2019
DOI: 10.1038/s41598-019-44167-6
|View full text |Cite
|
Sign up to set email alerts
|

In-situ detection based on the biofilm hydrophilicity for environmental biofilm formation

Abstract: A biofilm has a unique structure composed of microorganisms, extracellular polymeric substances (EPSs), etc., and it is layered on a substrate in water. In material science, it is important to detect the biofilm formed on a surface to prevent biofouling. EPSs, the major component of the biofilm, mainly consist of polysaccharides, proteins, nucleic acids, and lipids. Because these biomolecules have a variety of hydrophilicities or hydrophobicities, the substrate covered with the biofilm shows different wettabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…As ethanol reacts with the film when used as the solvent, pure water was used as a solvent for extracting crystal violet in this study. The use of pure water instead of ethanol as the solvent for extracting crystal violet can be one of the reasons for the greater variability than in biofilm quantification by crystal violet staining in previous studies [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…As ethanol reacts with the film when used as the solvent, pure water was used as a solvent for extracting crystal violet in this study. The use of pure water instead of ethanol as the solvent for extracting crystal violet can be one of the reasons for the greater variability than in biofilm quantification by crystal violet staining in previous studies [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4E,F, many PS3 cells as well as microbial clumps were observed on the surface. It has been regarded that electrode ‐ associated microbial biofilms can facilitate the transport of electrons between electrodes and cells, as well as among cells fixed within the film for power generation of MFCs 10,41 . A few bacterial genera, such as Geobacter , Shewanella , Synechocystis , and Rhodopseudomonas , have been reported to transfer electrons through nanowires (pili and flagella) directly 12,26,42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been regarded that electrode-associated microbial biofilms can facilitate the transport of electrons between electrodes and cells, as well as among cells fixed within the film for power generation of MFCs. 10,41 A few bacterial genera, such as Geobacter, Shewanella, Synechocystis, and Rhodopseudomonas, have been reported to transfer electrons through nanowires (pili and flagella) directly. 12,26,42,43 We observed that there were several extracellular filamentous structures along with the PS3 cells during the SEM examination ( Figure 4B), which were proposed to function as nanowires.…”
Section: Biofilm and Filamentous Structures Formed By Ps3mentioning
confidence: 99%
“…EPS, one of the main components of biofilms, is composed of polysaccharides, proteins, nucleic acids, and lipids (Tanaka et al, 2019). Since EPS can diversely characterize in water (e.g., hydrophilic or hydrophobic), it presents variances in the wettability of biofilms.…”
Section: Extracellular Polymeric Substances and Biofoulingmentioning
confidence: 99%